2019
DOI: 10.1128/aem.01887-19
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antibodies Provide Bank Voles with Strain-Specific Protection against Infection by the Lyme Disease Pathogen

Abstract: Multistrain microbial pathogens often induce strain-specific antibody responses in their vertebrate hosts. Mothers can transmit antibodies to their offspring, which can provide short-term, strain-specific protection against infection. Few experimental studies have investigated this phenomenon for multiple strains of zoonotic pathogens occurring in wildlife reservoir hosts. The tick-borne bacterium Borrelia afzelii causes Lyme disease in Europe and consists of multiple strains that cycle between the tick vector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Therefore, TBEV seroprevalence in small mammals is a good proxy for the occurrence of new infections in a month, although it is impossible to distinguish antibodies due to maternal transfer from those developed after a recent infection. In small mammals, maternal antibodies generally last from six to 10 weeks [ 46 , 47 , 48 ], but this duration is unknown for TBEV. We captured two juveniles aged 3–4 weeks according to their weight that were seropositive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TBEV seroprevalence in small mammals is a good proxy for the occurrence of new infections in a month, although it is impossible to distinguish antibodies due to maternal transfer from those developed after a recent infection. In small mammals, maternal antibodies generally last from six to 10 weeks [ 46 , 47 , 48 ], but this duration is unknown for TBEV. We captured two juveniles aged 3–4 weeks according to their weight that were seropositive.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this is provided by the positive association between neonatal antibody levels and the mother's own anti-strongyle antibody levels in the summer prior to giving birth. Previous experimental studies in captive rodents have demonstrated that maternal antibodies provide strain-specific protection which depends on the infection history of the mother [ 46 , 47 ]. Given that exposure to worms starts early, we would expect that all females would be sufficiently exposed to have developed an acquired immune response to strongyles by sexual maturity, despite exposure varying in time and space [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the subset of infected tissues, we found that the spirochete load was highest in the ears and the dorsal skin, and lower in internal organs like the heart, bladder, and ankle joints. Other studies on B. afzelii and B. burgdorferi sensu stricto (ss) in rodent hosts, have also found that the spirochete load is higher in the skin compared to internal organs like the bladder and heart [33,[36][37][38][39]. One explanation for this result is that the skin is important for the host-to-tick transmission of B. burgdorferi sl [21][22][23], whereas the internal organs (e.g., bladder, heart, and joints) are a deadend for spirochete transmission to ticks (39).…”
Section: Prevalence Of B Afzelii In the Tissues Of The Rodent Hostmentioning
confidence: 94%
“…The I. ricinus ticks came from the laboratory colony that has been maintained at the University of Neuchâtel since 1978. We used B. afzelii strains NE4049 and Fin-Jyv-A3 in this study because we have a history of successful experimental infections with these two strains [33,34,36,37]. Strain NE4049 was isolated from an I. ricinus tick in Switzerland, has multi-locus sequence type (MLST) 679, strain ID number 1887 in the Borrelia MLST database, and ospC major group (oMG) A10.…”
Section: Methodsmentioning
confidence: 99%